2014
DOI: 10.1111/cxo.12066
|View full text |Cite
|
Sign up to set email alerts
|

Personal consequences of work‐related physical discomfort: an exploratory study

Abstract: Background: Work-related physical discomfort has been reported in Australian optometrists. The purpose of this paper is to explore the personal consequences of work-related discomfort. Methods: Forty-seven optometrists with self-reported work-related discomfort participated in a 30-minute telephone or face-to-face interview related to ergonomics and physical comfort. Self-employed, employee, locum and retired optometrists participated. Four avenues were investigated; namely, description of discomfort, non-work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In particular, pain and discomfort in the neck and shoulder region is reported more frequently by eye care physicians than peers in other medical specialties (Kitzmann et al 2012). Consequences of this pain and physical discomfort include reduced working hours, regular pursuit of medical treatment, and job change (Long et al 2012a(Long et al , 2012b(Long et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, pain and discomfort in the neck and shoulder region is reported more frequently by eye care physicians than peers in other medical specialties (Kitzmann et al 2012). Consequences of this pain and physical discomfort include reduced working hours, regular pursuit of medical treatment, and job change (Long et al 2012a(Long et al , 2012b(Long et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sheedy, Hayes and Engle investigated the natures of various visual symptoms in different types of visual impairments and Buckhurst and colleagues assessed the benefits of different presbyopic corrections. Long and colleagues and Long, Burgess‐Limerick and Stapleton administered questionnaires about work‐related physical discomfort to optometrists.…”
mentioning
confidence: 99%
“…The risk of work-related musculoskeletal (MSK) pain among optometrists has become widely recognized by the profession and in the literature. [1][2][3] Preliminary research on the impact of work-related MSK pain on eye care professionals has found that MSK pain and discomfort can lead optometry professionals to seek alternate employment, be hospitalized and seek other medical treatment. 4 Other studies have found that improper work ergonomics can lead to poor productivity, disability and early retirement.…”
Section: Introductionmentioning
confidence: 99%